(untitled) (Altre Modernità, 2013)
This work aims to analyze the cultural history of the botanical species generally indicated as ’carob three’, through the correlation between the Mediterranean carob (Ceratonia siliqua) and its South American relative (Prosopis pallida, affinis, chilensis o julinflora). Although the biological relationship between the two plants is thin, they share a combination of cultural and symbolic significances common to different communities in different geographical and cultural areas. In particular this paper, based on a field research in the Northern coast of Peru, will examine the symbolic characteristics of the South American carob three in the peculiar area of the Santuario Histórico Bosque de Pómac, in the region of Lambayeque.